Les espaces de coworking : des instruments de résilience territoriale pour l’après-Covid ? - Divya Leducq (Netcom)
Over the past year, all new collaborative workspaces and third places, including coworking spaces (CWSs), have been affected by the pandemic. A systematic press review represents an original qualitative method to acquire contextualized secondary material through narratives and detailed cases in France. This research note reports the main results concerning the implemented strategies to cope with the effects of the crisis and regarding the increasing diversification of the remote workers using CWSs. In a future-oriented approach, we support the hypothesis that post-Covid19 coworking can be an effective tool for territorial resiliency based on several analytical perspectives: spatial scale, urban practices and public policies.